Addendum to memorandum of understanding between Universiti Teknologi MARA and Institut Jantung Negara Sdn Bhd / Fakulti Perubatan - Universiti Teknologi MARA, Fakulti Perubatan (Universiti Teknologi MARA (UiTM), 2020)
UiTM and IJN will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.